Pengaruh Konsentrasi Maleat Anhidrida Terhadap Persen Derajat Grafting dari Polietilen - Denny Akbar Tanjung (Mahesa Research Center, 2022)
This research aims to determine the maximum concentration of Maleat Anhidrida in grafting into the LLDPE chain with the help of Benzoyl Peroxide as an initiator. Mixing is done by the Blending method using an internal mixing tool. The titration results showed that the maximum percentage of grafting degree occurred at a concentration of 9% Maleat Anhidrida. The formation of new peaks at wave numbers 1707 and 1267cm-1 proves that grafting has taken place into the LLDPE monomer.